2009
DOI: 10.1523/jneurosci.1215-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

NR2A at CA1 Synapses Is Obligatory for the Susceptibility of Hippocampal Plasticity to Sleep Loss

Abstract: A loss in the necessary amount of sleep alters expression of genes and proteins implicated in brain plasticity, but key proteins that render neuronal circuits sensitive to sleep disturbance are unknown. We show that mild (4 -6 h) sleep deprivation (SD) selectively augmented the number of NR2A subunits of NMDA receptors on postsynaptic densities of adult mouse CA1 synapses. The greater synaptic NR2A content facilitated induction of CA3-CA1 long-term depression in the theta frequency stimulation range and augmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 64 publications
4
23
0
Order By: Relevance
“…This study revealed stress-induced increases in the hippocampal expression of NR2A and the NR2A/NR2B ratio ( Figure 3A, C), which were previously shown to accompany elevated anxiety (Boyce-Rustay & Holmes, 2006;Calabrese et al, 2012;Gao et al, 2010), impulsivity and aggression (Bortolato et al, 2012;Meyer et al, 2004), home cage hyperactivity and a stress-induced increase in peripheral concentrations of corticosterone (Huang et al, 2010;Longordo et al, 2009) in various conditions. A limitation of our study, however, is the need for confirmation that the mRNA changes result in corresponding changes in subunit protein levels and in altered synaptic function in the hippocampus.…”
Section: Discussionsupporting
confidence: 66%
“…This study revealed stress-induced increases in the hippocampal expression of NR2A and the NR2A/NR2B ratio ( Figure 3A, C), which were previously shown to accompany elevated anxiety (Boyce-Rustay & Holmes, 2006;Calabrese et al, 2012;Gao et al, 2010), impulsivity and aggression (Bortolato et al, 2012;Meyer et al, 2004), home cage hyperactivity and a stress-induced increase in peripheral concentrations of corticosterone (Huang et al, 2010;Longordo et al, 2009) in various conditions. A limitation of our study, however, is the need for confirmation that the mRNA changes result in corresponding changes in subunit protein levels and in altered synaptic function in the hippocampus.…”
Section: Discussionsupporting
confidence: 66%
“…This finding was correlated with a shift in the frequency needed to elicit LTD and LTP, decreasing the threshold frequency to induce LTD and increasing the threshold frequency to induce LTP. This group also observed that removal of NR2A subunits prevented the synaptic plasticity changes induced by sleep deprivation (Longordo et al 2009). However, these differences in subunit ratios and mediated current after sleep deprivation have not been observed by other research groups.…”
Section: N-methyl-d-aspartate (Nmda) Receptor and A-amino-3-hydroxy-5mentioning
confidence: 90%
“…Although both of these studies observed clear differences in trafficking and NMDA receptor-mediated current using extended periods of sleep deprivation, these findings conflict with findings from briefer periods of sleep deprivation (Vecsey et al 2009). Using electron microscopy, Kopp and colleagues found that 4 h of sleep deprivation by exposure to a novel environment and introduction to new nesting material increased the NR2A/NR2B NMDA-receptor subunit ratio as well as total NR2A subunits in the hippocampus (Kopp et al 2006;Longordo et al 2009). This finding was correlated with a shift in the frequency needed to elicit LTD and LTP, decreasing the threshold frequency to induce LTD and increasing the threshold frequency to induce LTP.…”
Section: N-methyl-d-aspartate (Nmda) Receptor and A-amino-3-hydroxy-5mentioning
confidence: 99%
“…Gene expression of plasticity-related molecules and the ability to induce LTP can be influenced both by the sleep-wake history (Guzman-Marin et al, 2006, Gilestro et al, 2009, Tartar et al, 2006, Vyazovskiy et al, 2008) as well as the phase of the circadian cycle (Claridge-Chang et al, 2001, Dana and Martinez, 1984, Chaudhury et al, 2005). For example, sleep deprivation selectively increases the number of NR2A subunits of the glutamate NMDA receptors (Longordo et al, 2009), and a change in the ratio of NR2A/NR2B subunits shifts the threshold for subsequent LTP induction (Xu et al, 2009). In addition, high levels of endogenous adenosine from sleep loss impairs LTP through an adenosine A1 receptor mediated effect (Arrigoni et al, 2009).…”
Section: Discussionmentioning
confidence: 99%